International research collaboration University of Nottingham, United Kingdom and Universiti Teknologi MARA, Malaysia - Ramli, Anis Safura (Faculty of Medicine, 2022)
The UK-Malaysia Joint Partnership Call on Non-Communicable Diseases project titled ‘Reducing Premature Coronary Artery Disease in Malaysia by Early Identification of Familial Hypercholesterolaemia’ marked another level of an international research collaboration between University of Nottingham (UoN), United Kingdom and Universiti Teknologi MARA (UiTM), Malaysia. It is a collaborative research project between the Institute of Pathology, Laboratory and Forensic Medicine (IPPerForM), UiTM, the Department of Primary Care Medicine, UiTM and the Faculty of Medicine and Health Sciences, UoN.